1. The problem statement, all variables and given/known data lim (3/n)^(2n) n→ ∞ 2. Relevant equations L'hopital's rule: lim F(a)/G(a) is indeterminate form, then the limit can be written as lim F'(a)/G'(a) x → a x→ a 3. The attempt at a solution lim e^[ln(3/n)^(2n)] = lim e^(2n * ln(3/n)) n→ ∞ n → ∞ 2n * ln(3/n) = [2 * ln(3/n)] / (n^-1 ) and applying L.h., [2 * (n/3) * (-3/n^2)]/(-n^-2) reduces to, 2 * n, and clearly, plugging in n = infinity is wrong. Where did I go wrong, and what can I do to fix this problem?